2019
DOI: 10.1021/acsami.9b15303
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Triplet–Triplet Annihilation of Blue Fluorescent Organic Light-Emitting Diodes by Generating Excitons in Trapped Charge-Free Regions

Abstract: Three new anthracene-cored molecules, 3,3′-(5-(10-(naphthalen-1-yl)­anthracen-9-yl)-1,3-phenylene)­dipyridine (AP3Py-Na), 3,3′-(5-(10-(naphthalen-2-yl)­anthracen-9-yl)-1,3-phenylene)­dipyridine (AP3Py-2Na), and 9,10-bis­(3,5-di­(pyridin-3-yl)­phenyl)­anthracene (ADP3Py), were synthesized to be used as an efficiency-enhancement layer (EEL) in blue fluorescent organic light-emitting diodes. Insertion of a very thin EEL (3 nm) between the deep blue emitting layer (EML) and the electron transport layer enhanced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Using TTA material as light-emitting host in OLEDs is an efficient approach to produce blue, green or red emissions when doped with different dopants. [28,[234][235][236] In this strategy, singlet and triplet excitons are formed directly in host materials where TTA takes place. Singlet excited states generated via TTA are transferred to the guest materials through Förster resonance energy transfer.…”
Section: Doped Layer Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Using TTA material as light-emitting host in OLEDs is an efficient approach to produce blue, green or red emissions when doped with different dopants. [28,[234][235][236] In this strategy, singlet and triplet excitons are formed directly in host materials where TTA takes place. Singlet excited states generated via TTA are transferred to the guest materials through Förster resonance energy transfer.…”
Section: Doped Layer Structurementioning
confidence: 99%
“…2021, 33, 2100704 displaying TTA character. [236,247] Lu and co-workers found a CT-featured naphthalimide derivative (CzPhONI) with a quite small exchange energy but a lower lying 3 ππ* state than the 3 CT state, which is capable of harvesting triplets through TTA. [248] Another naphthalimide compound (E)-2-(4-(tbutyl)phenyl)-6-(2-(6-(diphenylamino)naphthalen-2-yl)vinyl)-1H-benzo[de] isoquinoline-1,3(2H)-dione (NA-TNA, Figure 13b) with intramolecular CT character was exploited by the same group, by using diphenylamine, vinylnaphthalene and 1,8-naphthalimide as the electron donor (D), π-bridge and electron acceptor (A), respectively.…”
Section: Doped Layer Structurementioning
confidence: 99%
“…Specifically for blue-emitting devices recent progress in both efficiency and stability has been achieved by employing TTA. [51,52] Regarding stability of OLEDs and PLEDs TTA can also play an important role. First, a higher efficiency due to TTA means for a given light-output a lower current, so less polarons, which reduces triplet-polaron interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some exceptions that the delayed fluorescence is determined in the case of a large ΔE ST in the exciplex, which might originate from triplet-triplet annihilation (TTA). [58][59][60][61][62] To clarify the different luminescent mechanisms of exciplex, i.e., either TADF or TTA, Monkman's group compared three combinations of exciplexes, i.e., m-MTDATA:TPBi, TPD:TPBi, and TPD:OXD-7. [63] After elucidating the photophysical data, it was concluded that the exciplex m-MTDATA:TPBi with a small gap between charge transfer singlet ( 1 CT) state and locally excited triplet ( 3 LE) state respectively for the constituting donor and acceptor could exhibit almost pure TADF features.…”
Section: Exciplex From the Mixture Of Donor And Acceptormentioning
confidence: 99%